Proceedings of the Food and Drug Administration's public workshop on new red blood cell product regulatory science 2016. Issue 1 (15th December 2017) - Vostal, Jaroslav G.; Buehler, Paul W.; Gelderman, Monique P.; Alayash, Abdu I.; Doctor, Alan; Zimring, James C.; Glynn, Simone A.; Hess, John R.; Klein, Harvey; Acker, Jason P.; Spinella, Philip C.; D'Alessandro, Angelo; et al.
Abstract : The US Food and Drug Administration (FDA) held a workshop on red blood cell (RBC) product regulatory science on October 6 and 7, 2016, at the Natcher Conference Center on the National Institutes of Health (NIH) Campus in Bethesda, Maryland. The workshop was supported by the National Heart, Lung, and Blood Institute, NIH; the Department of Defense; the Office of the Assistant Secretary for Health, Department of Health and Human Services; and the Center for Biologics Evaluation and Research, FDA. The workshop reviewed the status and scientific basis of the current regulatory framework and the available scientific tools to expand it to evaluate innovative and future RBC transfusion products. A full record of the proceedings is available on the FDA website (http://www.fda.gov/BiologicsBloodVaccines/NewsEvents/WorkshopsMeetingsConferences/ucm507890.htm ). The contents of the summary are the authors' opinions and do not represent agency policy.